Takikardia Ventrikular pada Infark Miokard Akut dengan Elevasi Segmen ST Anterior Septal: Laporan Kasus - Sequeira Saldanha, Luzelia Marta (Cermin Dunia Kedokteran, 2025)
Introduction: Fatal ventricular tachyarrhythmias such as ventricular tachycardia (VT) or ventricular fibrillation (VF) are the most frequent cause of sudden cardiac death. In-hospital mortality of VT in STEMI was a 4- to 5-fold increase compared to STEMI without ventricular tachyarrhythmia; VT and VF were also initially thought to be the most common causes of out-of-hospital cardiac arrest. Late VT (occurs beyond 24-48 hours of STEMI onset) is a predictor for worse prognosis. Case: A 49-year-old female presented with continuous chest pain for 5 days and a rapid heartbeat (palpitation) for 4 days before hospital admission. Initial examination revealed VT and ST elevation on ECG, leading to a diagnosis of anteroseptal STEMI with VT. Treatment included aspirin, clopidogrel, heparin, isosorbide dinitrate, bisoprolol, and simvastatin. The VT resolved about 2 hours after the initial treatment, and the evolution of STEMI (on ECG) was observed. Conclusion: Early recognition and prompt treatment for VT patients can prevent hemodynamic instability and reduce mortality.